2005
DOI: 10.1111/j.1462-2920.2004.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promotion abilities and microscale bacterial dynamics in the rhizosphere of Lupin analysed by phytate utilization ability

Abstract: SummaryIn the rhizosphere, phosphorus (P) levels are low due to P uptake into the roots.Rhizobacteria live on carbon (C) exuded from roots, and may contribute to plant nutrition by liberating P from organic compounds such as phytates. We isolated over 300 phytate (Na-inositol hexa-phosphate; Na-IHP)-utilizing bacterial strains from the rhizosheath and the rhizoplane of Lupinus albus (L.). Almost all of the isolates were classified as Burkholderia based on 16S rDNA sequence analysis.Rhizosheath isolates culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 39 publications
2
84
0
3
Order By: Relevance
“…A number of bacteria with phytate-hydrolyzing activity that are able to improve plant phosphorus nutrition was isolated from white lupine (Lupinus albus) rhizosphere in Japan [60]. Almost all of these strains were classified as representatives of Burkholderia family.…”
Section: Microbial Phytases As Molecular Biofertilizersmentioning
confidence: 99%
“…A number of bacteria with phytate-hydrolyzing activity that are able to improve plant phosphorus nutrition was isolated from white lupine (Lupinus albus) rhizosphere in Japan [60]. Almost all of these strains were classified as representatives of Burkholderia family.…”
Section: Microbial Phytases As Molecular Biofertilizersmentioning
confidence: 99%
“…This suggests that microorganisms are in fact a key driver in regulating the mineralization of phytate in soil and their presence within the rhizosphere may compensate for a plants inability to otherwise acquire P directly from phytate. Bacteria with ability to mineralize phytate have been isolated from the rhizosphere and further work to assess the ecology and in situ function of such microorganisms in soil environments is warranted along with further assessment of their potential for development as inoculants (Unno et al, 2005;Jorquera et al, 2011).…”
Section: Mineralization Of Organic Pmentioning
confidence: 99%
“…Richardson 87) observed that the ability of pasture plants to acquire P from phytate was improved by the presence of soil microorganisms. In Japan, Unno et al 116) isolated diverse bacteria with phytate-utilizing ability from the rhizosphere of white lupin (Lupinus albus). Almost all isolates were classified as members of the genus Burkholderia and some isolates significantly promoted plant growth.…”
Section: Phytate-producing Bacteria As Plant Growth-promoting Agentsmentioning
confidence: 99%